Production of physiologically complete drinking water using modified reverse osmosis membrane elements - Tyvonenko, Artem; Mitchenko, Tetiana; Homaniuk, Oleksii; Vasilyuk, Sergey; Kosogina, Iryna; Mudryk, Rostyslav (Eastern-European Journal of Enterprise Technologies, 2023)
Drinking water prepared using the most effective and popular reverse osmosis method is absolutely safe but for the most part does not meet the requirements for physiologically complete water. The latter must meet, in addition to the basic requirements, the following requirements: salt content, at least 100, and not more than 1000 mg/dm3; total hardness; in the range of 1–7.0 mmol/dm3. Now, to fulfill these requirements, the stage after desalting employs various methods of domineralization of reverse osmosis water, each of which has certain disadvantages. This paper considers the task of obtaining safe physiologically complete water immediately after the stage of membrane desalting by using modified reverse osmosis membrane elements with the predefined selectivity. The study object was the process of obtaining reverse osmosis membrane elements with the predefined selectivity by modifying them with sodium hypochlorite solution for use in the process of obtaining physiologically complete drinking water. The required level of selectivity of modified elements was calculated to obtain safe physiologically complete water from starting water, depending on its salt content. Thus, for the starting water with a salt content of 200–300 mg/dm3, the specified selectivity of the membrane element should be no more than 60 % at a temperature of 25 °C. Rational conditions for conducting the modification process for obtaining a membrane element with such exact selectivity have been established. The nature of the influence of changes in water temperature on the selectivity of the modified element was studied. A prototype of the modified element was tested in a vending machine for pouring water, which purified tap water in the city of Kyiv, with a salt content of 230 mg/dm3 at a temperature of 8–12 °C. The test results showed the possibility of one-stage obtaining safe physiologically complete water by reverse osmosis using a modified membrane element with the predefined selectivity of 50 %.